2018
DOI: 10.1152/physiolgenomics.00070.2018
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis signatures of gut microbiota in coronary artery disease

Abstract: Gut microbiota dysbiosis has been considered to be an important risk factor that contributes to coronary artery disease (CAD), but limited evidence exists about the involvement of gut microbiota in the disease. Our study aimed to characterize the dysbiosis signatures of gut microbiota in coronary artery disease. The gut microbiota represented in stool samples were collected from 70 patients with coronary artery disease and 98 healthy controls. 16S rRNA sequencing was applied, and bioinformatics methods were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
106
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(136 citation statements)
references
References 44 publications
13
106
4
1
Order By: Relevance
“…The results showed that six of these genera were positively correlated with vitamin D3, including Subdoligranulum ( R 2 = 0.181, P = .0023, Figure F), Ruminiclostridium ( R 2 = 0.1217, P = .014, Figure G), Intestinimonas ( R 2 = 0.2036, P = .0011, Figure H), Pseudoflavonifractor ( R 2 = 0.1014, P = .0257, Figure I), Paenibacillus ( R 2 = 0.089, P = .0373, Figure J), and Marvinbryantia ( R 2 = 0.08173, P = .0464, Figure K). It is worth noting that Subdoligranulum is an anti‐inflammatory bacterium shown to be significantly depleted in patients with coronary artery disease . Furthermore, a previous study regarding inflammatory bowel disease (IBD), a condition in which vitamin D deficiency seems to play a role in intestinal inflammation, showed that specific gut species including Subdoligranulum were increased after oral vitamin D administration in IBD patients but not CTR.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that six of these genera were positively correlated with vitamin D3, including Subdoligranulum ( R 2 = 0.181, P = .0023, Figure F), Ruminiclostridium ( R 2 = 0.1217, P = .014, Figure G), Intestinimonas ( R 2 = 0.2036, P = .0011, Figure H), Pseudoflavonifractor ( R 2 = 0.1014, P = .0257, Figure I), Paenibacillus ( R 2 = 0.089, P = .0373, Figure J), and Marvinbryantia ( R 2 = 0.08173, P = .0464, Figure K). It is worth noting that Subdoligranulum is an anti‐inflammatory bacterium shown to be significantly depleted in patients with coronary artery disease . Furthermore, a previous study regarding inflammatory bowel disease (IBD), a condition in which vitamin D deficiency seems to play a role in intestinal inflammation, showed that specific gut species including Subdoligranulum were increased after oral vitamin D administration in IBD patients but not CTR.…”
Section: Resultsmentioning
confidence: 99%
“…A more significant finding has been the decrease of Bacteroidetes and increase of Firmicutes, Escherichia-Shigella and Enterococcus in the gut of CAD patients suggesting Figure 1. Gut microbiota may produce beneficial as well as deleterious effects in coronary artery disease patients, which is due to the production of useful or harmful metabolites that the shift in microbiota may be one of contributing factor in the development of coronary heart disease [23,24,26]. It is possible to suggest that due to alterations in the profile of gut microbiota, there are changes in the metabolism in the gut and subsequently, altered metabolic products may gain entry in the blood circulation to produce deleterious effects.…”
Section: Discussionmentioning
confidence: 99%
“…Other bacterial species that were relatively less represented in the gut of CAD patients included Subdoligranulum, Roseburia, and Eubacterium rectale. It further signifies that gut microbiota dysbiosis is an important risk factor for the development of CAD and identification of changes in its composition may be potentially employed for its diagnosis [26].…”
Section: Gut Microbiota Composition and Its Possible Use As A Non-invmentioning
confidence: 99%
“…[41] Regarding the speci c taxonomy of the gut microbiome, the genus Flavonifractor was enriched in βblocker users in both the full and PS-matched cohorts. Flavonifractor is associated with several diseases, such as obesity, [42] atrial brillation, [43] coronary artery disease, [44] major depressive disorder, [45] and bipolar disorder [46], and medications (antidiabetic drugs, such as Metformin and Glucagon-like peptide 1…”
Section: Discussionmentioning
confidence: 99%
“…It can convert quercetin or other avonoids into acetic acid and butyric acid [48] and is also correlated with oxidative stress and in ammation. [46] Taken together, Flavonifractor is signi cantly less abundant in the subjects with obesity, [42] atrial brillation, [43] or coronary artery disease, [44] thus, the increased abundance of Flavonifractor by β-blocker treatment may have a potential bene t in cardiovascular disease via gut microbiota regulation. However, an enriched Flavonifractor in major depressive disorder [45] and bipolar disorder [46] could also link the relationship between β-blockers and major depressive disorder or bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%